2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35431
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Power of Data Analytics to Examine Engineering Students’ Experiences and Outcomes

Abstract: Her research interests include learning experiences and outcomes assessment in postsecondary education, research methodologies and data analytics in engineering education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We began with building upon our previous literature review [1] of the articles published by the Journal of Engineering Education (JEE) from 2011 to 2021 that focused on undergraduate engineering students' development. We used the database we had created but extracted articles on high school and undergraduate students' experiences in reference to the relevant research topics identified from our methodological review of articles published by four major engineering education journals [16].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We began with building upon our previous literature review [1] of the articles published by the Journal of Engineering Education (JEE) from 2011 to 2021 that focused on undergraduate engineering students' development. We used the database we had created but extracted articles on high school and undergraduate students' experiences in reference to the relevant research topics identified from our methodological review of articles published by four major engineering education journals [16].…”
Section: Methodsmentioning
confidence: 99%
“…However, not all important factors that literature reveals in relation to engineering pathways are included in the theory. For example, science identity formation in high school [81], and engineering professional identity in postsecondary education [1], are important to individuals' engineering pathways; however, identity , is not an explicit component of SCCT. Therefore, how to add these factors into SCCT can be future work on engineering pathways.…”
Section: Connecting With the Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations